Продовольча безпека України та напрями її забезпечення - Мостенська, Тетяна Леонідівна; Федулова, Ірина Валентинівна; Мостенська, Тетяна Геннадіївна (My University, 2012)
Розглянуто теоретичні підходи до визначення продовольчої безпеки. Це дало можливість визначити та охарактеризувати групи показників та індикаторів, що визначають стан продовольчої безпеки країни. В статті наведено розрахунки значень показників продовольчої безпеки України. Індикатори продовольчої безпеки представлено в динаміці за період з 2000 по 2010 роки. Визначено основні чинники впливу на продовольчу безпеку та охарактеризовано їх дію. Theoretical trips to the definition of food security are reviewed. This made it possible to identify and characterize groups and indicators that define the state of the country's food security. The paper presents the calculation of indicators of food security in Ukraine. Food security indicators are presented for the period 2000 - 2010. The main factors of influence on food security are identified and its action are characterized. The figures for the three groups of criteria were calculated. This made to possible to set of problems in the form of food security in Ukraine. The trends of support of food security are defined.
Keywords: продовольча безпека; показники продовольчої безпеки; зовнішні та внутрішні загрози продовольчої безпеки; food safety; food security indicators; external and internal threats to food security; кафедра економіки праці та менеджменту